ЕБС-ийн бага ангийн монгол хэлний сурах бичиг дэх уран зохиолын нэр томьёоны тогтвортой хэрэглээг цахим хэл шинжлэлийн үүднээс бүртгэсэн нь - Т., Батбямба; Г., Нарантунгалаг; Э., Уранбилэг; Ч., Алтангэрэл (Mongolian Studies, 2022)
This paper aimed to define the sustainable use of the terminology of literature. To reach the aim, we created the electronic source of the vocabulary of textbooks of 1-5 grades of general education schools Mongolian language textbooks using the Cyrillic Mongolian writing program of phonetic transcription which was built by the School of Applied Science and Engineering of the National University of Mongolia (Ch. Altangerel, J.Purev) and AntConc software (Laurence Anthony) of Japan. Based on the electronic source of vocabulary, we registered the terminology of literature, calculated the frequency of terminology, and compared the textbooks of the same grades as well as different grades.